A Review on Performance of Chemical, Natural and Composite Coagulant - Azizan Bin Omar, Mohamad; Shaylinda Binti Mohd Zin, Nur; Nor Aishah binti Mohd Salleh, Siti (International Journal of Engineering and Technology, 2018)
Coagulation and flocculation process are commonly used in the treatment of water and wastewater. Normally the chemical coagulant (inorganics coagulants) is widely used as primary coagulant due to its availability, show good efficiency, cheaper and ease to handle. However, from the previous study, the application of conventional coagulant causes environmental effect and consumed large dosage. Many studies were carried out to overcome this problem such as the development of new chemical coagulant, utilization of natural coagulant, application of dual coagulant and composite coagulant. Development of new chemical coagulant such as pre-hydrolysing coagulant (combination of two or more chemical coagulant) and synthetic cationic polymers that richer with positive charge ion are seen able to enhance the removal efficiency at a lower dosage. However, this coagulant still is made from chemical substances that probably contribute to the toxicological issues. To date, natural coagulant is widely explored due to its capability, besides free from physical, and chemical changes in the treated water. However, most of the natural coagulant as single coagulant is not effective in removal compared to the chemical coagulant. Thus, to improve the efficiency while combining the best properties of both coagulants, the development of composite coagulant made from natural and chemical coagulant is necessary. The objective of this paper is to gives an overview of the performance of single, dual, and composite coagulants in order to develop the novel composite coagulant.Â Â